Spodbujati in ohraniti razvojne ambicije: Global Entrepreneurship Monitor Slovenia 2003 - Rebernik, Miroslav; Tominc, Polona; Glas, Miroslav; Širec, Karin (University of Maribor Press, 2004)
Promote and maintain development ambitions: Global Entrepreneurship Monitor Slovenia 2003. One of very encouraging findings of this publication, based on the GEM methodology and the data obtained in 2003, are the high ambitions of entrepreneurs who are at the very beginning of the entrepreneurial path. Growth orientation of Slovenian entrepreneurs, derived from their intentions, show they are very optimistic about what will happen with their ventures in the coming years. However, gradual diminishing of their development plans is too high to be attributed only to naivety and unrealistic expectations of emerging entrepreneurs, especially considering the extremely high mortality rate of new ventures. Apparently, the business environment in Slovenia is still very unfavourable, so maintaining growth ambitions is seen as an important strategic task. Study also underlined the strategic orientation to increase of the level of entrepreneurial skills, creation of positive attitudes towards entrepreneurship, developing the access to finance, development of female entrepreneurship, further development of enterprise policy and programs, and transfer of R&D results. Entrepreneurial ambitions need to be nurtured and creative individuals must have an environment in which ambitions will survive and flourish.